Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4103/aer.aer_106_18
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic protective effect of dexmedetomidine after partial hepatectomy surgery: A prospective controlled study

Abstract: Background: Inflow occlusion of the portal triad is a common blood loss-reducing method during hepatectomy which may induce ischemic-reperfusion injury of the remaining parts of the liver. Dexmedetomidine is used for reducing ischemic-reperfusion injury in hepatectomy. Aim: The aim of this study was to assess the protective effect of dexmedetomidine on liver after partial hepatectomy using inflow occlusion. Setting and Design: This prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…TBIL content was reported in two studies (Ding et al, 2018;Taman and Elhefnawy, 2019). Pooled results with a fixed effect model revealed that dexmedetomidine inhibited the increase in TBIL level at 24 h after surgery compared with control (WMD −4.51, 95% CI: −7.32-−1.71, p 0.002, I 2 0%) (Figure 2G).…”
Section: Outcome Measuresmentioning
confidence: 65%
See 4 more Smart Citations
“…TBIL content was reported in two studies (Ding et al, 2018;Taman and Elhefnawy, 2019). Pooled results with a fixed effect model revealed that dexmedetomidine inhibited the increase in TBIL level at 24 h after surgery compared with control (WMD −4.51, 95% CI: −7.32-−1.71, p 0.002, I 2 0%) (Figure 2G).…”
Section: Outcome Measuresmentioning
confidence: 65%
“…A detailed overview of PRISMA flow chart for database searching and study identification is presented in Figure 1. Eight studies enrolling 468 participants were included in this meta-analysis (Wang et al, 2014;Tan et al, 2016;Zhang et al, 2017;Ding et al, 2018;Jiang et al, 2018;Taman and Elhefnawy, 2019;Xing et al, 2020;Zhang et al, 2020). Characteristics of included RCTs and study participants were summarized in Tables 1, 2.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations